O‘QUVCHILARDA DIZAYN TUSHUNCHASINING TA’RIFLANISHI, SHAKLLANISH DAVRLARI VA XUSUSIYATLARI - Berdimbetova, A.Dj. (SCIENCE and SOCIETY, 2025)
The article describes the definition of the concept of design among students, the periods of formation and design activity, in contrast to simple design, design work is aimed at ensuring that the object is beautiful, compact, easy to maintain and cheap, given its functional function. Information is provided on the social, cultural, economic, educational significance of design projects in society and the development of design knowledge, skills, and design thinking among students for design-based design.